1996
DOI: 10.1118/1.597678
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric considerations for a multileaf collimator system

Abstract: A commercial linear accelerator with a factory-fitted multileaf collimator (MLC) was commissioned for clinical use. Measurements made of dosimetric parameters included central axis depth-dose, field-size factors, wedge factors, penumbra, and leaf leakage for the 6-MV and 15-MV photon beams available on this accelerator. The depth-dose characteristics, output factors, and transmission factors were similar to those reported in the literature for a machine by the same manufacturer with a standard treatment head. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…Figure 1 shows a cross-section of the Elekta head design. Measurements by Palta et al, 23 have demonstrated S c for the upper-jaw replacement system can be accurately calculated by using the equivalent square of the MLC blocked field area.…”
Section: A2a Determination Of Field Size For S Cmentioning
confidence: 99%
“…Figure 1 shows a cross-section of the Elekta head design. Measurements by Palta et al, 23 have demonstrated S c for the upper-jaw replacement system can be accurately calculated by using the equivalent square of the MLC blocked field area.…”
Section: A2a Determination Of Field Size For S Cmentioning
confidence: 99%
“…It is typically a complex function of the field size projected to the isocenter and depends on the design of the treatment unit collimation system. [38][39][40][41] The phantom scatter factor, S p , and the TPR together correct for differences from the reference conditions in scatter and attenuation, with S p primarily accounting for changes in scatter and TPR accounting for the effects of tissue attenuation as well as changes in scattering conditions with depth. These factors depend on the effective equivalent square [42][43][44] of the irradiated area ͑at SPD͒, which is typically estimated from the field shape defined by the MLC or poured blocks.…”
Section: Manual Photon Calculationsmentioning
confidence: 99%
“…The collimator scatter factor is determined using the X-ray collimator jaw settings, with an off-axis factor applied for asymmetric jaw settings. However, Palta and colleagues found that for the Elekta linacs (MLC replacing the upper collimator jaws) the MLC field shape was a determining factor in selecting the appropriate output factor for their system (Palta et al 1996). Their results showed that MLC dosimetry is clearly dependent on machine design differences, and so because treatment machine MLC designs are still changing, each institution is advised to carefully study the impact of the MLC on their basic MU calculation procedure before introduction in the clinic.…”
Section: Monitor Unit Calculation For Mlcmentioning
confidence: 91%
“…Monitor unit calculations for asymmetric jaws are only slightly more complex than for symmetric jaws (Gibbons 2000). Typically, one simply applies an offaxis ratio (OAR) or off-center ratio (OCR) correction factor that depends only on the distance from the machine's central axis to the center of the independently collimated open field (Palta et al 1996;Slessinger et al 1993). A more complex system that accounts for independent jaw settings, field size, and depth has also been described (Chui et al 1986;Rosenberg et al 1995).…”
Section: Monitor Unit Calculation For Asymmetric Collimatorsmentioning
confidence: 99%